The effect of cadence on cycling efficiency and local tissue oxygenation - Jacobs, R. D.; Berg, K. E.; Slivka, D. R.; Noble, J. M. (The Journal of Strength and Conditioning Research, 2013)
The purpose of this study was to compare 3 cycling cadences in efficiency/economy, local tissue oxygen saturation, heart rate, blood lactate, and global and local rating of perceived exertion (RPE). Subjects were 14 trained cyclists/triathletes (mean age 30.1 ± 5.3 years; VO2 peak 60.2 ± 5.0 ml/kg/min) who performed three 8-minute cadence trials (60, 80, and 100 rpm) at 75% of previously measured peak power. Oxygen consumption and respiratory exchange ratio were used to calculate efficiency and economy. Results indicated that both efficiency and economy were higher at the lower cadences. Tissue oxygen saturation was greater at 80 rpm than at 60 or 100 rpm at minute 4, but at minute 8, tissue oxygen saturation at 80 rpm (57 ± 9%) was higher than 100 rpm (54 ± 9%, p = 0.017) but not at 60 rpm (55 ± 11%, p = 0.255). Heart rate and lactate significantly increased from minute 4 and minute 8 (p < 0.05) of submaximal cycling. Local RPE at 80 rpm was lower than at 60 or 100 rpm (p < 0.05). It was concluded that (a) Trained cyclists and triathletes are more efficient and economical when cycling at 60 rpm than 80 or 100 rpm. (b); Local tissue oxygen saturation levels are higher at 80 rpm than 60 and 100 rpm; (c). Heart rate and blood lactate levels are higher with cadences of 80 and 100 than 60 rpm; and (d). Local and global RPE is lower when cycling at 80 rpm than at 60 rpm and 100 rpm. A practical application of these findings is that a cadence of 60 rpm may be advantageous for performance in moderately trained athletes in contrast to higher cadences currently popular among elite cyclists.